2023
DOI: 10.2147/ijn.s395246
|View full text |Cite
|
Sign up to set email alerts
|

Angiopep-2 Modified Exosomes Load Rifampicin with Potential for Treating Central Nervous System Tuberculosis

Abstract: Background Central nervous system tuberculosis (CNS-TB) is the most devastating form of extrapulmonary tuberculosis. Rifampin (RIF) is a first-line antimicrobial agent with potent bactericidal action. Nonetheless, the blood-brain barrier (BBB) limits the therapeutic effects on CNS-TB. Exosomes, however, can facilitate drug movements across the BBB. In addition, exosomes show high biocompatibility and drug-loading capacity. They can also be modified to increase drug delivery efficacy. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Currently, the investigation of using Exos as a delivery system for antimicrobial agents is still in its preliminary phases. Li et al [ 45 ] investigated the antimicrobial potential of angiopep-2 modified exosomes load rifampicin (ANG-Exo-RIF) on Mycobacterium tuberculosis strain H37Rv. Their findings revealed that the MIC of RIF, Exo-RIF, and ANG-Exo-RIF was 0.25 μg/mL against the H37Rv strain, indicating that the encapsulation of rifampicin in exosomes did not affect its antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the investigation of using Exos as a delivery system for antimicrobial agents is still in its preliminary phases. Li et al [ 45 ] investigated the antimicrobial potential of angiopep-2 modified exosomes load rifampicin (ANG-Exo-RIF) on Mycobacterium tuberculosis strain H37Rv. Their findings revealed that the MIC of RIF, Exo-RIF, and ANG-Exo-RIF was 0.25 μg/mL against the H37Rv strain, indicating that the encapsulation of rifampicin in exosomes did not affect its antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…The isolated exos (50 μg/mL, total protein) were co‐incubated with the DSPE‐PEG 2000 ‐FA (50 μg/mL) for 30 min with shaking at 37°C to prepare Astro‐exo‐FA. TMZ was loaded into the Astro‐exo‐FA through electroporation to obtain TMZ@Astro‐exo‐FA, according to a previous study 24 . Thus, TMZ (200 μg) and exos (200 μg) were mixed with PBS to a final volume of 500 μL in an electroporation cuvette.…”
Section: Methodsmentioning
confidence: 99%
“…TMZ was loaded into the Astro-exo-FA through electroporation to obtain TMZ@Astro-exo-FA, according to a previous study. 24 Thus, TMZ (200 μg) and exos (200 μg) were mixed with PBS to a final volume of 500 μL in an electroporation cuvette.…”
Section: Production Of Engineered Tmz@astro-exo and Tmz@astro-exo-famentioning
confidence: 99%
“…Li et al. designed a novel BMSC-exosome-based nanoparticle, ANG-Exo-RIF, loaded with rifampicin and the brain-targeting peptide angiopep-2 ( 97 ). ANG-Exo-RIF exhibited high targeting ability and penetration, excellent anti-TB activity, and good biocompatibility, which is promising for CNS-TB treatment ( Figure 4 ).…”
Section: Therapeutic Applications Of Exosomes In Tb Treatmentmentioning
confidence: 99%